Conceptual framework for strengthening nurse-initiated management of antiretroviral therapy training and implementation in North West province - Sheillah H. Mboweni; Lufuno Makhado (AOSIS, 2020)
Background: The implementation of nurse-initiated management of antiretroviral therapy (NIMART) management training is a challenge in the primary health care (PHC). It is evident from the literature reviewed and the data obtained from the North West province that gaps still exist. There is no conceptual framework providing guidance to NIMART training and implementation. Aim: Therefore, the aim of this study was to develop a conceptual framework to strengthen NIMART training and implementation in the North West province to improve patients and human immunodeficiency virus (HIV) programme outcomes. Setting: The study was conducted in the North West Province, South Africa. Methods: A pragmatic, explanatory, sequential, mixed-methods research design was followed. A descriptive and explorative programme evaluation design was used. Data were collected from two sources: antiretroviral therapy (ART) statistics from District Health Information System (DHIS) Tier.net of 10 PHC facilities to evaluate and determine the impact of NIMART on the HIV programme and five focus group discussions conducted amongst 28 NIMART nurses and three HIV programme managers to describe challenges influencing NIMART training and implementation. Results: The study revealed that there was low ART initiation compared to the number of clients who tested HIV-positive. There was poor monitoring of patients on ART, which was evident in the low viral load collection and suppression, high loss to follow-up and deaths related to HIV. Challenges exist and this was confirmed by the qualitative findings, including human resource ratios, training and mentoring and the entire absence of a conceptual framework or model that guides training and implementation. Conclusion: The study findings were conceptualised to describe and develop a framework needed to facilitate and influence NIMART training and implementation to improve the HIV programme and patient outcomes. Dickoff, James and Wiedenbach's practice-oriented theory and Donabedian's structure process outcomes model provided a starting point in the ultimate development of the framework. Although the study was limited to the North West province's PHC clinics and community health centres and did not include hospitals, it is of high significance as there is no such conceptual framework in the province or in even South Africa.